2023
DOI: 10.1007/s00586-023-07587-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various options for decompression of degenerated lumbar spine motion segments on the range of motion: a biomechanical in vitro study

Abstract: Background Lumbar spinal stenosis is a common disease in the aging population. Decompression surgery represents the treatment standard, however, a risk of segmental destabilization depending on the approach and extent of decompression is discussed. So far, biomechanical studies on techniques were mainly conducted on non-degenerated specimens. This biomechanical in vitro study aimed to investigate the increase in segmental range of motion (ROM) depending on the extent of decompression in degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
7
2
1
Order By: Relevance
“…Our cohort, with 84% of the cases having a decompression only as their spinal stenosis surgery, suggests that the prevalence of lumbar spinal stenosis itself constitutes a risk for THA reoperation, possibly through the same mechanisms as in the setting of spinal deformities. In addition, it seems that lumbar spine decompression without fusion at least does not increase the spinal stiffness, supporting the idea that the spinal pathology itself may increase the risk, and not necessarily only the surgical procedure [17,18].…”
Section: Discussionmentioning
confidence: 83%
“…Our cohort, with 84% of the cases having a decompression only as their spinal stenosis surgery, suggests that the prevalence of lumbar spinal stenosis itself constitutes a risk for THA reoperation, possibly through the same mechanisms as in the setting of spinal deformities. In addition, it seems that lumbar spine decompression without fusion at least does not increase the spinal stiffness, supporting the idea that the spinal pathology itself may increase the risk, and not necessarily only the surgical procedure [17,18].…”
Section: Discussionmentioning
confidence: 83%
“…Laminectomy is a common surgical method for lumbar stenosis. According to the results of finite element analysis and cadaveric specimen experiments [ 29 , 30 ], unilateral laminectomy had a minimal impact on the segmental ROM. Zander et al conducted finite element analysis by establishing a lumbar spine model to compare the biomechanical effects of graded facetectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Postacchini et al reported that 3 out of 32 patients suffered from significant segment disability after total laminectomy [ 32 ]. In Lener et al‘s study [ 30 ], when complete laminectomy was performed with bilateral partial facetectomy, segmental ROM increased by 20% ± 15.9, 11% ± 9.9, and 19% ± 10.5% in flexion-extension, lateral bending, and axial rotation, respectively. In our study, due to the preservation of facet joints, the percentage increase in segmental ROM was smaller compared to cadaveric specimen experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they assessed the range of motion of the single motion segment, without assessing any effects on the adjacent segment ( Costa et al, 2018 ). Lener et al (2023) , reported that the intersegmental motion of four-lumbar-vertebrae specimens significantly increased after laminectomy, as opposed to hemilaminectomy. The ROM of the adjacent motion segment was not significantly affected by the amount of decompression ( Lener et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%